Trichoscopic and Clinico-Morphological Evaluation of Tinea Capitis - Lavina Meghwal; Sharad Mehta; Lalit Kumar Gupta; Manisha Balai; Asit Mittal (Wolters Kluwer Medknow Publications, 2024)
Introduction: Tinea capitis (TC) is a common fungal infection of the scalp, especially in children. Trichoscopy is a noninvasive technique that allows rapid and magnified in vivo observation of the hair with the visualization of morphologic features that are often imperceptible to the naked eye. Aim: This study aimed to evaluate the usefulness of trichoscopy in clinical diagnosis and to study various clinico-morphological patterns of TC. Materials and Methods: This cross-sectional, observational study included 140 clinically diagnosed cases of TC seen during a period of 1 year (April 2021 to March 2022). All patients were evaluated using a dermoscope (DermLite DL4 Multispectral 3 Gen, San Juan Capistrano, CA, USA,10×). Results: The prevalence rate of TC in this study was 2.69 per thousand population. The most common clinical variant was gray patch followed by kerion and black dot, and the most common etiological agent was Trichophyton tonsurans. The characteristic trichoscopic features were as follows: comma hairs (80%), followed by corkscrew hairs (68.6%), bent hairs (54.2%), zigzag hairs (35.7%), and morse code-like hairs (15%). Other findings included scaling (89.2%), followed by black dot (67.1%), broken hairs (42.8%), and crusting and pustules (32.1% each). Comma and corkscrew-shaped hairs were most common in the black dot type, whereas zigzag, bent hairs, and morse code hairs were common in the gray patch type of TC. There was a significant association between trichoscopic findings and type of TC. Conclusion: Trichoscopy can be considered a novel tool for rapid diagnosis and selection of the appropriate therapy and in the monitoring of treatment efficacy in TC.